A national survey of MRI safety practices in Ghana. Issue 12 (December 2017) - Piersson, Albert Dayor; Gorleku, Philip Nii
Abstract: Objective: The aim of the present study was to assess current MRI safety practices among MRI facilities in Ghana, and their compliance with the 2013 American College of Radiology (ACR) guidance document on MR safe practices. Material and methods: A questionnaire developed from the 2013 ACR Guidance Document was used to collect information on magnetic field strengths, MR safety policy and compliance, patient screening, emergency preparedness, infection control, MRI safety accessories, equipment safety, signage and barriers, report of adverse incidents, and access and communication. Results: Out of the 13 MRI facilities identified, response rate of 92% was obtained. Six (50%) facilities indicated they have MRI safety policy and have it present and readily available to facility staff. Five (42%) facilities indicated they have handheld magnets, and 1(8%) has ferromagnetic detection system. Only one (8%) had crash carts. Seven (58%) facilities have zone 4 clearly marked with a red light and lighted sign stating "The Magnet is On". One (8%) recorded projectile incident and fire outbreak. Eight (67%) facilities have direct visual observation of access corridors to zone IV. Conclusion: There was compliance in some areas of MRI safety practice, however there were some shortfalls which need to be addressed. We therefore recommend improvement in the following areas: (1) establishment, implementation, and maintenance of current MRI safety policy, (2) patient screening, (3) provision of training and routine drills on emergency response protocols with documentations, (4) emergency preparedness, and (5) provision of colour codes for equipment used within MRI environment.